2020
DOI: 10.1093/bjc/azaa032
|View full text |Cite
|
Sign up to set email alerts
|

Live Facial Recognition: Trust and Legitimacy as Predictors of Public Support for Police Use of New Technology

Abstract: Facial recognition technology is just one of a suite of new digital tools police and other security providers around the world are adopting in an effort to function more safely and efficiently. This paper reports results from a major new London-based study exploring public responses to Live Facial Recognition (LFR): a technology that enables police to carry out real-time automated identity checks in public spaces. We find that public trust and legitimacy are important factors predicting the acceptance or rejec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…While effective, such measures are controversial and spur debate about privacy. A recent study on this subject found that legitimacy and public trust in the police are crucial in this matter, as they influence acceptance of facial recognition technology and may diminish concerns about privacy (Bradford et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While effective, such measures are controversial and spur debate about privacy. A recent study on this subject found that legitimacy and public trust in the police are crucial in this matter, as they influence acceptance of facial recognition technology and may diminish concerns about privacy (Bradford et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, procedurally fair processes and interactions indicate to people working in an organization that power within it is wielded in a normatively justifiable manner-that managers and supervisors "do the right things for the right reasons" (Suchman, 1995;Jackson & Bradford, 2019). This sense of normative alignment between the power-holder's values and those of subordinates motivates a feeling that the orders and instructions of power-holders within the organization should be obeyed (Jackson et al, 2012;Tyler et al, 2007;Trinkner et al, 2018) and that police are justified in using force and employing new technologies (Tyler & Wakslak, 2004;Bradford et al, 2020). Here, this is a concept of legitimacy within law enforcement agencies that is entirely in accordance with that used in the procedural justice literature, where the concern is between those agencies and the people they police (Huq et al, 2017).…”
Section: Psychological Mechanism Of Promoting Changementioning
confidence: 99%
“…Second, will people trust the police to use this technology appropriately? A growing body of research has explored public trust as a critical factor that shapes public attitudes and acceptance towards police uptake of new technology (see among many others Ariel et al, 2018 ; St Louis et al, 2019 ; Meijer & Wessels, 2019 ; Ridgeway, 2019 ; Bradford et al, 2020 ). Such trust is of course not “free-floating” or entirely prior to the development under consideration, but is developed via the direct, vicarious and mediated experiences people have of policing (Jackson et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%